State of animus among Brazilians: influence of socioeconomic context? - Célia Landmann Szwarcwald; Francisco Inácio Bastos; Maria Angela Pires Esteves
Preliminary results of the World Health Survey, conducted in Brazil in 2003, indicate a high frequency of self-perceived problems related to state of animus. The main objective of the present study is to investigate the hypothesis that material deprivation and job insecurity are important determinants of self-reported mental problems, such as feelings of depression and anxiety. Analysis of factors associated with self-perceived problems related to state of animus was performed with multivariate logistic regression models. Among females, key factors associated with feelings of depression and anxiety were level of education and unemployment after controlling for age, presence of long duration disease or disability and of body injury limiting everyday activities. Among males, feelings of depression were most strongly associated with unemployment, followed by poverty (as measured by a household asset indicator), with being married (or cohabiting) showed a protector effect. With regard to severe feelings of anxiety, only unemployment contributed significantly. These findings highlight the influence of social and economic contexts, beyond strictly individual characteristics, on the health of Brazilians.